PROTECTIVE EFFECT OF CAMEL MILK AS ANTI-DIABETIC SUPPLEMENT: BIOCHEMICAL, MOLECULAR AND IMMUNOHISTOCHEMICAL STUDY - Mansour, Ahmed A.; Nassan, Mohammed A.; Saleh, Osama M.; Soliman, Mohamed M. (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Diabetes is a serious disease affects human health. Diabetes in advanced stages is accompanied by general weakness and alteration in fats and carbohydrates metabolism. Recently there are some scientific trends about the usage of camel milk (CM) in the treatment of diabetes and its associated alterations. CM contains vital active particles with insulin like action that cure diabetes and its complications but how these effects occur, still unclear. Materials and Methods: Seventy-five adult male rats of the albino type divided into five equal groups. Group 1 served as a negative control (C). Group 2 was supplemented with camel milk (CM). Diabetes was induced in the remaining groups (3, 4 and 5). Group 3 served as positive diabetic control (D). Group 4 served as diabetic and administered metformin (D+MET). Group 5 served as diabetes and supplemented with camel milk (D+CM). Camel milk was supplemented for two consecutive months. Serum glucose, leptin, insulin, liver, kidney, antioxidants, MDA and lipid profiles were assayed. Tissues from liver and adipose tissues were examined using RT-PCR analysis for the changes in mRNA expression of genes of carbohydrates and lipid metabolism. Pancreas and liver were used for immunohistochemical examination using specific antibodies. Results: Camel milk supplementation ameliorated serum biochemical measurements that altered after diabetes induction. CM supplementation up-regulated mRNA expression of IRS-2, PK, and FASN genes, while down-regulated the expression of CPT-1 to control mRNA expression level. CM did not affect the expression of PEPCK gene. On the other hand, metformin failed to reduce the expression of CPT-1 compared to camel milk administered rats. Immunohistochemical findings revealed that CM administration restored the immunostaining reactivity of insulin and GLUT-4 in the pancreas of diabetic rats. Conclusion: CM administration is of medical importance and helps physicians in the treatment of diabetes mellitus.